Decadal Weakening of Abyssal South China Sea Circulation. Issue 20 (17th October 2022) - Zhu, Yaohua; Yao, Jingxin; Li, Shujiang; Xu, Tengfei; Huang, Rui Xin; Nie, Xunwei; Pan, Haidong; Wang, Yonggang; Fang, Yue; Wei, Zexun
Abstract: The global ocean mass has significantly changed during recent decades, which may induce changes in the abyssal ocean circulation. Due to the lack of in situ observations, the response of the abyssal South China Sea (SCS) circulation to ocean mass changes remains unclear. The ocean state estimate, Estimating the Circulation and Climate of the Ocean (ECCO), provides the long‐term ocean mass changes in terms of ocean bottom pressure (OBP). Here we use the ECCO OBP data to quantify decadal changes in the abyssal SCS circulation and reveal a weakening trend. The OBP gradient trend manifests in forms of an anomalous anticyclonic circulation that is intensified by topographic effects along the continental slopes to reduce the existing abyssal circulation. The weakening abyssal circulation corresponds to the weakening Luzon Strait overflow that yields a decreasing vorticity budget in the abyssal SCS. Plain Language Summary: Caused by global warming, ice melt and long‐term atmospheric forcing changes, ocean mass has been increased and redistributed over the past decades. The changes in ocean mass distribution may lead to changes in abyssal ocean circulation. The changes in the abyssal South China Sea (SCS) circulation remains unclear due to the lack of in situ observations. This study uses the Estimating the Circulation and Climate of the Ocean (ECCO) ocean state estimate to quantify decadal changes in the abyssal SCS circulation. Our analysis of the ECCO ocean bottom pressure data reveals a weakening trend in the abyssal SCS circulation that is consistent with the recently ascertained weakening Luzon Strait overflow. Key Points: Trends in the ECCO ocean bottom pressure (OBP) gradients indicate a decadal weakening abyssal South China Sea (SCS) circulation The weakening circulation coincides with the weakening Luzon Strait overflow that yields a decreasing vorticity budget in the abyssal SCS The anomalous anticyclonic circulation is dominated by OBP gradient trends and intensified by topographic effects along continental slopes